Цинк і його значення для росту та статевого розвитку дітей - Большова, О. В.; Пахомова, В. Г. (Clinical Endocrinology and Endocrine Surgery, 2011)
Literature data of the clinical, epidemiological and experimental results concerning role of zinc in a function of the growth regulation system, physical and pubertal development of a child are presented and analyzed in the article. A sharp zinc decrease in the blood and hair of children with growth-hormone deficiency and constitutional delay against a background of significant decrease in GH, IGF-1,IGF-BP-3 levels was demonstrated by own results. The revealed disorders in zinc content are the basis for including the zinc drugs in complex therapy of children with growth retardation and pubertal delay.